Change in Medication-Associated Fall Risk Among Older Adults After Admission for Fall-Related Trauma. Issue 6 (November 2021) - Gross, Amber; Elliott, David P.; Lasky, Tiffany; Samanta, Damayanti; Kafka, Wesley; Murphy, Miranda; Patel, Apexa
Abstract : Background: As the population ages, it is predicted that approximately 40% of all patients who experience fall-related trauma will be 65 years of age and older. Most injuries in older adults are caused by falls that are the result of multiple contributing factors including home hazards, comorbidities, frailty, and medications. A variety of medications have been associated with falls, specifically those with sedating and anticholinergic effects. The drug burden index can be used to quantify sedating and anticholinergic drug burden, with higher scores being associated with reduced psychomotor function. Objective: Assess the medication-associated fall risk on admission and discharge for older patients admitted to a trauma nurse practitioner service. Methods: Retrospective, observational study of patients managed by trauma nurse practitioners at a Level 1 trauma center between January 1, 2018, and December 31, 2019. Patients were included if they were at least 65 years of age, the primary diagnosis for the admission was fall-related trauma, and length of stay was at least 7 days. Results: A total of 172 patients were included in the study. The drug burden index was significantly higher at discharge than admission ( M = 1.4, SD = 0.9 vs. M = 1.9, SD = 0.9) as was the total number of medications ( M = 11.0, SD = 5.2 vs. M = 15.1, SD = 5.8). Conclusions: Medication-related fall risk was increased during admission due to fall-related trauma. Patients were discharged with a higher sedating and anticholinergic burden than on admission, which increases risk for future falls.